Inventory of major insects of Jatropha curcas L. (Euphorbiaceae) and their natural enemies in Southern Benin. - Datinon, B.; Glitho, A.I.; Tamò, Manuele; Amevoin, K.; Goergen, Georg E.; Douro-Kpindou, O.K. (2013)
Inventory of insects associated with Jatropha curcas L. (Euphorbiaceae) was conducted from June 2011 to May 2012 at 5 sites in southern and central Benin. Thirty-two major insect pests and 14 natural enemies, including 6 parasitoids and 8 predators, were recorded. The most important phytophagous species were Stomphastis thraustica (Meyrick) (Lepidoptera: Gracillariidae), Aulacophora africana (Weise) (Coleoptera: Chrysomelidae), Altica sp. (Coleoptera: Apionidae), Lagria villosa (Fabricius) (Coleoptera: Lagriidae), Paracoccus marginatus Williams and Gramara de Willink (Hemiptera: Pseudococcidae), Denticera nr divisella (Duponchel) (Lepidoptera: Pyralidae), Nezara viridula (Linnaeus) (Hemiptera: Pentatomidae), Calidea dregei Germar (Heteroptera: Scutelleridae), and Riptortus dentipes Fabricius (Hemiptera: Alydidae). Almost all recovered parasitoids were obtained from caterpillars of D. nr divisella; a pest moth causes significant damage to flowers and young capsules of J. curcas. Within this guild the ichneumonid wasp Syzeuctus nr hessei Benoit proved to be the most effective parasitoid against D. nr divisella in all 5 sites, with parasitism rate averaging 63%.